2020
DOI: 10.1155/2020/5497041
|View full text |Cite
|
Sign up to set email alerts
|

Aidi Injection, Compound Kushen Injection, or Kanglaite Injection: Which Is the Best Partner with Systemic Chemotherapy for Patients with HCC? A Network Meta‐Analysis

Abstract: Objective. The aim of this network meta-analysis (NMA) was to explore the effectiveness of different traditional Chinese medicine injections (TCMIs) combined with systemic chemotherapy for the treatment of hepatocellular carcinoma (HCC). Methods. A comprehensive search for randomized controlled trials (RCTs) was performed with regard to different TCMIs for treating HCC in seven electronic databases up to November 2019. The quality assessment of the included RCTs was conducted according to the Cochrane risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Clinically, KLT has synergistic effects with radiotherapy and chemotherapy, it has been used in the adjuvant treatment of various tumors such as lung cancer ( Hailang et al, 2020a ; Li et al, 2020 ), breast Cancer ( Liu S. et al, 2021 ), hepatocellular carcinoma ( Liu et al, 2019 ; Dou et al, 2020 )and colorectal cancer ( Mao et al, 2020 ). The main effects targeted the improvements of clinical efficacy, performance status, KPS score, immune function and the reduction of the side effects of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, KLT has synergistic effects with radiotherapy and chemotherapy, it has been used in the adjuvant treatment of various tumors such as lung cancer ( Hailang et al, 2020a ; Li et al, 2020 ), breast Cancer ( Liu S. et al, 2021 ), hepatocellular carcinoma ( Liu et al, 2019 ; Dou et al, 2020 )and colorectal cancer ( Mao et al, 2020 ). The main effects targeted the improvements of clinical efficacy, performance status, KPS score, immune function and the reduction of the side effects of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the NMA conducted by Dou et al (2020), which included only 20 RCTs retrieved from 7 databases, was run by a Bayesian fixed-effect model with treatments being ranked by SUCRA scores. They reported that Kanglaite injection has better performance than Aidi injection and compound Kushen injection in tumor response when combining with systemic chemotherapy.…”
Section: Contradiction With Previous Studiesmentioning
confidence: 99%
“…They reported that TACE + TCM exhibits the best treatment response in advanced HCC patients. On the other hand, Dou et al (2020) compared the effectiveness of Aidi injection, compound Kushen injection, and Kanglaite injection as adjuvant treatments to systemic chemotherapy for HCC patients and reported that Kanglaite injection outweighs the other two products in tumor response. However, there is still no evidence assessing all forms of TCM formulations and informing which one works best for each defined outcome.…”
Section: Introductionmentioning
confidence: 99%
“… 2018 ; Dou et al. 2020 ). Clinical studies have found that it can enhance tumour sensitivity to chemotherapy drugs, enhance immunity, reduce toxicity and side effects, and that it exhibits significant synergy (Xiao et al.…”
Section: Introductionmentioning
confidence: 99%